APRENDENDO COM A PRÁTICA: PROCESSO DE GERMINAÇÃO DE FEIJÃO-DECORDA (VIGNA UNGUICULATA) SUBMETIDO A DOIS TIPOS DE AMBIENTE - GOMES, J. D.; OLIVEIRA, J. R. M.; MARTIN, L. V. R.; BERNARDINO, W. S; NAKAGAKI, J. M. (ANAIS DO ENIC, 2016)
-